2011
DOI: 10.1371/journal.pone.0018727
|View full text |Cite
|
Sign up to set email alerts
|

The Human Splice Variant Δ16HER2 Induces Rapid Tumor Onset in a Reporter Transgenic Mouse

Abstract: Several transgenic mice models solidly support the hypothesis that HER2 (ERBB2) overexpression or mutation promotes tumorigenesis. Recently, a HER2 splice variant lacking exon-16 (Δ16HER2) has been detected in human breast carcinomas. This alternative protein, a normal byproduct of HER2, has an increased transforming potency compared to wild-type (wt) HER2 receptors. To examine the ability of Δ16HER2 to transform mammary epithelium in vivo and to monitor Δ16HER2-driven tumorigenesis in live mice, we generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
102
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 20 publications
(33 reference statements)
6
102
0
Order By: Relevance
“…Both of these alterations could explain the clinical failure of trastuzumab 55, 56, 57, 58, 59, 60. The Δ16HER‐2, a type of oncogenic variant caused by the in‐frame deletion of exon 16 in the extracellular domain of HER‐2, is reported to comprise 4–9% of total HER‐2 transcripts 56, 61. The Δ16HER‐2 variant, when expressed at high levels, harbours enhanced transforming activity compared with wild‐type HER‐2 54.…”
Section: The Her‐2 Mutations and Variantsmentioning
confidence: 99%
“…Both of these alterations could explain the clinical failure of trastuzumab 55, 56, 57, 58, 59, 60. The Δ16HER‐2, a type of oncogenic variant caused by the in‐frame deletion of exon 16 in the extracellular domain of HER‐2, is reported to comprise 4–9% of total HER‐2 transcripts 56, 61. The Δ16HER‐2 variant, when expressed at high levels, harbours enhanced transforming activity compared with wild‐type HER‐2 54.…”
Section: The Her‐2 Mutations and Variantsmentioning
confidence: 99%
“…Interestingly, those studies also revealed a direct correlation between node status and delta16HER2 mRNA expression (Mitra et al, 2009), implicating delta16HER2 in human BC progression. Further confirmation of delta16HER2 intrinsic oncogenicity came from our recent generation a mouse line transgenically expressing the human delta16HER2 variant using a bicistronic vector encoding both delta16HER2 and luciferase reporter genes under the MMTV promoter (Marchini et al, 2011). Our transgenic line was characterized by a higher tumor incidence as well as a shorter latency (about 8 weeks of age) compared to the MMTVhuHER2 transgenic model, which developed human WT HER2-overexpressing spontaneous mammary tumors after 28 weeks of age (Finkle et al, 2004;Marchini et al, 2011).…”
Section: Delta16her2 Splice Variantmentioning
confidence: 82%
“…The delta16HER2 variant was expressed on mammary tumor cells as cell surface-associated phosphorylated stable homodimers and monomers, and its downstream signals were significantly coupled to an activated Src kinase. In this transgenic model, about 5 copies of the delta16HER2 transgene were sufficient to drive early transformation in contrast to 30-50 copies of WT HER2 transgene needed to develop mammary tumors in the MMTVhuHER2 model (Finkle et al, 2004;Marchini et al, 2011). Very recently, Alajati et al (2013) provided further in vitro evidence that delta16HER2 is able to increase invasion and proliferation and also to decrease apoptosis either in two-or three-dimensional conditions.…”
Section: Delta16her2 Splice Variantmentioning
confidence: 93%
See 2 more Smart Citations